(untitled) (Journal of Health, Population and Nutrition, 2011)
Integration of infant- and child-feeding index (ICFI) addressing the multidimensional child-feeding practices into one age-specific summary index is gaining importance. This cross-sectional study was aimed at understanding the association between the ICFI and the nutritional status of 259 children, aged 6-23 months, who attended the paediatric outpatient department of the Dhaka Medical College Hospital in Bangladesh. The mean length-for-age z-score (LAZ) of children aged 12-23 months was significantly (p<0.05) higher among those who were at the upper ICFI tercile compared to those who were at the middle or lower ICFI tercile (-2.01 and -3.20 respectively). A significant correlation was found between the ICFI and the LAZ (r=0.24, p=0.01 and r=0.29, p=0.01) in children aged 6-8-months and 12-23-months. Multivariable analysis, after adjusting for potential confounders, also found a significant association between the ICFI and the LAZ (β=0.13, p=0.03). The predictive capability of the proposed ICFI on nutritional status of children, especially length-for-age, needs to be further evaluated prospectively among healthy children in the community. Key words: Cross-sectional studies; Child-feeding practices; Child nutrition; Child nutritional status; Infant- and child-feeding index; Infant-feeding practices: Infant nutrition; Infant nutritional status; Bangladesh DOI: http://dx.doi.org/10.3329/jhpn.v29i4.8450 JHPN 2011; 29(4): 349-356